Neolithic Britain : the transformation of social worlds - Ray, Keith (Keith W.), 1954-; Thomas, Julian, 1959- (Oxford University Press, 2018)
Neolithic Britain' is an up to date, concise introduction to the period of British prehistory from c. 4000-2200 BCE, covering key material and social developments, and reflecting on the nature of cultural practices, tradition, genealogy, and society across nearly two millennia.